A fluorescent nanoparticle probe based on sugar-substituted tetraphenylethene for label-free detection of galectin-3. Issue 43 (24th October 2019) - Zhang, Zhiling; Yu, Yong; Zhao, Yueyue; Ng, Ka Ming
Abstract : An AIE-active nanoparticle probe decorated with galactoside residues is designed and developed for label-free detection of galectin-3 with enhanced specificity, showing promising applications in cancer diagnoses. Abstract : Galectin-3 is a vital biomarker for cancer progression. An aggregation-induced emission (AIE)-active nanoparticle probe is designed and synthesized for label-free detection of galectin-3 based on carbohydrate–protein interactions. The probe employs tetraphenylethene (TPE) as the fluorescent core structure and N -acetyllactosamine (LacNAc) as galactoside residues and self-aggregates into uniform nanoparticles with multiple binding sites on the surface targeting galectin-3. Upon crosslinking of the nanoparticles and galectin-3, large complexes are formed and a significant fluorescence change is measured, allowing rapid, sensitive and specific detection of galectin-3 via a fluorometric assay. Its demonstrated superior anti-interference ability and applicability in serum samples offer promising applications in cancer diagnoses.